Development of Electronic Student Worksheets based on Problem-based Learning (PBL) in Trigonometry - Prayuti, Amarta; Makmuri, Makmuri; Wijayanti, Dwi Antari (Program Studi Pendidikan Matematika FMIPA Universitas Negeri Jakarta, 2023)
This research aims to develop learning media in the form of electronic student worksheets based on the Problem-based Learning in trigonometry material for class X Senior High School. This learning media can be used in class or independently. The method used in this study is the research and development method or Research and Development (RnD) which refers to the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). After being tested, the researcher entered the evaluation stage, namely processing the data obtained from the results of the expert validation and trials. The material and language expert validation test scores were 83.33%, media validation tests were 93.48%, teacher validation tests were 99.31%, trials on students in small groups were 91.1%, and trials on students in large groups were 84.2 %. Based on these results obtained an average percentage of 90,284%. From the results of the effectiveness test obtained an average value of 98.27. It can be concluded that Problem-based Learning on trigonometry material can be interpreted as very feasible to be used as learning media for teachers and students.